Point mutants of Moloney murine leukemia virus that fail to package viral RNA: evidence for specific RNA recognition by a "zinc finger-like" protein sequence. - Gorelick, R J (1988)
All retroviruses encode a nucleic acid-binding or nucleocapsid protein that is believed to be associated with RNA in the virion. Further, all retroviral nucleocapsid proteins contain either one or two copies of the sequence Cys-Xaa2-Cys-Xaa4-His-Xaa4-Cys. The conservation of this sequence suggested that it is important for virus replication, and its resemblance to the "zinc-finger" sequences found in eukaryotic transcription factors raised the possibility that it recognizes specific sequences in viral RNA during retrovirus assembly. We used oligonucleotide-directed mutagenesis to generate a series of mutations in the nucleocapsid protein-coding region of Moloney murine leukemia virus. These mutations changed single amino acids, including each of the cysteines, to serine. The mutant viral genomes direct the synthesis of virus particles; these particles lack detectable viral RNA but do contain significant levels of cellular RNAs. Thus it appears that the mutations have destroyed the ability of the viral proteins to specifically package viral RNA during virus assembly. We propose that the conserved sequence in retroviral nucleocapsid proteins functions in RNA sequence recognition and suggest that it is evolutionarily related to the zinc fingers that recognize specific sequences in double-stranded DNA.